2000
DOI: 10.1007/s004380050044
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of centromeric regions on the molecular linkage map of rice (Oryza sativa L.) using centromere-associated sequences

Abstract: Genetic mapping of centromeres has been a challenge for plant geneticists. The objective of this study was to develop a new strategy for determining the locations of centromeric regions on genetic maps by mapping centromere-associated sequences, to make it possible to define the centromeric region of each chromosome as a single Mendelian locus on the molecular linkage map. Two DNA probes containing sequences specifically associated with the centromeres of grass species were used for genetic mapping. The centro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…Three-way crosses have been applied successfully in rice to map and identify QTLs for wide-compatibility (Wang et al 1998), to map centromeric regions (Wang et al 2000), and to map R genes (Wang and Xiao 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Three-way crosses have been applied successfully in rice to map and identify QTLs for wide-compatibility (Wang et al 1998), to map centromeric regions (Wang et al 2000), and to map R genes (Wang and Xiao 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The triangles in the bacterial blight resistance and blast resistance QTLs, detected using the same population as was used to construct the framework map, indicate the logarithm-of-odds peaks of the resistance effects. The filled circles represent the centromeric regions identified previously (Wang et al 2000a) co-localize with resistance QTLs identified in barley, bean, rice and potato (Faris et al 1999;Geffroy et al 2000;Trognitz et al, 2002;Xiong et al 2002;Ramalingam et al 2003). Thus, the candidate-gene approach may provide a means for pinpointing the genes that underlie resistance QTLs.…”
Section: Analyses Of the Sequences And Expression Patterns Of Defensementioning
confidence: 97%
“…It ensures proper cell division and stable transmission of the genetic material (Wang et al 2000). Elucidating the composition and structure of centromeres can be of use to understand its functional roles, including chromosome segregation, karyotypic stability, and artificial chromosome-based cloning (Wu et al 2004).…”
Section: Discussionmentioning
confidence: 99%